2016
DOI: 10.1111/jocn.13478
|View full text |Cite
|
Sign up to set email alerts
|

Working with complexity: experiences of caring for mothers seeking residential parenting services in New South Wales, Australia

Abstract: Australian residential parenting services have a significant role in supporting mothers and their families who are experiencing parenting difficulties. It frequently provides early intervention that helps minimise later emotional and physical problems. Nurses are well placed to work with and support mothers with complex histories. Acknowledgement is required that this work is stressful and nurses need to be adequately supported and educated to manage the complex presentations of many families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…There has been minimal research into the complexity of work and the services provided at EPCs (Fowler, Schmied, Dickinson, & Dahlen, ). This is the first published study that provides a description of nurses’ clinical decision‐making in regard to postnatal psychosocial assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been minimal research into the complexity of work and the services provided at EPCs (Fowler, Schmied, Dickinson, & Dahlen, ). This is the first published study that provides a description of nurses’ clinical decision‐making in regard to postnatal psychosocial assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Future research is need that involves observation as well as interviews to enable insight into the interaction between the nurse and the mother and the critical thinking processes, and to gain the context and the influences of the physical environment on the interaction (Mulhall, ). However, prior research conducted within Tresillian investigating the satisfaction of parents with the collaborative approach between nurse and parents has clearly demonstrated that the nurses work in partnership with the parents (Fowler et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, early parenting services (EPSs) provide support to parents of children from birth to preschool age who are experiencing complex parenting difficulties requiring specialist and multidisciplinary intervention. Care is provided in partnership with the family for issues such as infant feeding, sleep and behavioural problems and maternal perinatal mental health concerns (Australasian Association of Parenting and Child Health (AAPCH), 2016; Fowler et al, 2016). These EPSs vary in size and funding sources and may offer residential and day stay services as part of the parenting services (Bennett and Cooke, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of issues experienced by the women admitted to the two RPS has been clearly demonstrated. This complexity requires a high level of skill and ongoing mental health education (Fowler, Schmied, Dahlen, & Dickinson, ). While nursing is the predominate discipline within RPS, interprofessional collaboration is essential with clear internal and external referral pathways to enable timely and appropriate support (Bennett, Hauck, Radford, & Bindahneem, ).…”
Section: Discussionmentioning
confidence: 99%